Investigation of the bio-resistance of insulating protective coatings modified by polymeric petroleum resins - Nykulyshyn, Irena; Pikh, Zorian; Gnatush, Svitlana; Gnativ, Zoriana; Chajkivska, Ruslana (Eastern-European Journal of Enterprise Technologies, 2016)
Basic patterns of modification of bitumen composites by polymeric petroleum resins (PPR) are processed. Creation of new highly effective metal protecting compositions and study of their action patterns is an important scientific problem. It is found that introduction of PPR to the insulating petroleum bitumen improves the anticorrosive properties of protective coatings for underground pipelines. The adhesive strength of petroleum bitumen coatings is investigated. The mechanism of influence of the PPR components on the technical and operational properties of the compositions is considered. It is shown that the compositions on the basis of insulation bitumen BNI-IV-3, modified by cooligomeric dark PPR have higher anticorrosive characteristics and demonstrate bio-resistance to soil sulfate-reducing bacteria of the genus Desulfovibriodesulfuricans, especially corrosive for pipeline steel. Polymeric petroleum resins as modifiers significantly increase the inhibitory properties of the bitumen matrix and its resistance to soil bacteria. The absence of the catalyst extraction stage significantly reduces the bitumen modification cost. The results of the study of electroinsulating and anticorrosive characteristics of petroleum bitumen mastics, modified by the products of cooligomerization of hydrocarbon pyrolysis by-products confirmed the efficiency of the above materials and compositions on their basis in the protection of main oil and gas pipelines.